(untitled) (Ustozlar uchun, 2025)
Inclusive education is an educational approach that ensures equal learning opportunities for all learners, regardless of their physical, intellectual, social, emotional, linguistic, or other differences. This article explores the concept of inclusive education, its core principles, practical implementation strategies, and the challenges faced in modern educational systems. The study highlights the importance of inclusive practices in promoting equity, social justice, and quality education for all.